2016
DOI: 10.1038/srep31665
|View full text |Cite
|
Sign up to set email alerts
|

The γ-Protocadherin-C3 isoform inhibits canonical Wnt signalling by binding to and stabilizing Axin1 at the membrane

Abstract: The 22 γ-Protocadherin (γ-Pcdh) adhesion molecules encoded by the Pcdhg gene cluster play critical roles in nervous system development, including regulation of dendrite arborisation, neuronal survival, and synaptogenesis. Recently, they have been implicated in suppression of tumour cell growth by inhibition of canonical Wnt signalling, though the mechanisms through which this occurs remain unknown. Here, we show differential regulation of Wnt signalling by individual γ-Pcdhs: The C3 isoform uniquely inhibits t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 89 publications
0
48
0
Order By: Relevance
“…In any case, our in vivo KO results are strongly supported by the demonstration that that overexpression of γ-Pcdhs in vivo has the opposite effect on cortical spine density as does KO, and that γ-Pcdhs can suppress the potentiation of spine density by Nlg1 overexpression in hippocampal neurons. We suggest that γ-Pcdh function may be differentially regulated by distinct cis -interaction partners, either through their extracellular domains as observed here for Nlg1 or through intracellular signaling partners of their cytoplasmic domains, and that these may vary across neuronal subsets or developmental stages (Keeler et al, 2015a; Mah and Weiner, 2016; Mah et al, 2016). …”
Section: Discussionmentioning
confidence: 63%
“…In any case, our in vivo KO results are strongly supported by the demonstration that that overexpression of γ-Pcdhs in vivo has the opposite effect on cortical spine density as does KO, and that γ-Pcdhs can suppress the potentiation of spine density by Nlg1 overexpression in hippocampal neurons. We suggest that γ-Pcdh function may be differentially regulated by distinct cis -interaction partners, either through their extracellular domains as observed here for Nlg1 or through intracellular signaling partners of their cytoplasmic domains, and that these may vary across neuronal subsets or developmental stages (Keeler et al, 2015a; Mah and Weiner, 2016; Mah et al, 2016). …”
Section: Discussionmentioning
confidence: 63%
“…Mice in which only the ubiquitiously-expressed C3, C4, and C5 Pcdhg exons have been deleted phenocopy the null in many respects, while those lacking only the sparsely-expressed A1, A2, and A3 Pcdhg exons are viable and fertile [48]. This is consistent with the existence of distinct, non-redundant roles for one or more C-type γ-Pcdhs, a possibility borne out by the demonstration that γ-Pcdh-C3, uniquely among γ-Pcdhs, can interact with Axin1 to inhibit canonical Wnt signaling [49]. …”
Section: The Clustered Protocadherinsmentioning
confidence: 83%
“…We subsequently sought to elucidate the specificity of Wnt pathway suppression by γ-Pcdh isoforms, and to identify the molecular mechanisms through which it is achieved [204]. Using the TOPFLASH assay, in which HEK293 cells transfected with reporter constructs that yield a quantifiable luciferase signal upon exposure to Wnt3a, as well as quantitative PCR (qPCR) for Wnt target genes, we confirmed that the γ-Pcdh-C3 isoform, specifically, inhibits the canonical transcriptional pathway.…”
Section: Regulation Of Wnt Signaling By Pcdhsmentioning
confidence: 92%
“…Surprisingly, however, we found that 13 other γ-Pcdh isoforms can actually potentiate β-catenin/TCF/Lef luciferase reporter activity in response to Wnt3a. We determined that the variable cytoplasmic domain (VCD), unique to each γ-Pcdh isoform, is important in this regulation of Wnt signaling: expression of constructs encoding only the VCD of C3 or A1 isoforms was sufficient to, respectively, suppress or potentiate Wnt signaling [204]. We identified Axin1, a key component of the destruction complex, as an evolutionarily-conserved physical interactor of the γ-Pcdh-C3 VCD, and showed that the C3 VCD competes with Dvl for binding to the DIX domain of Axin1.…”
Section: Regulation Of Wnt Signaling By Pcdhsmentioning
confidence: 99%